PAS Synonymous as Opposition : A Study of Post GE15 - Syed Sopi, Saiyid Radzuwan; Ambak, Ahda (Advances in Humanities and Contemporary Studies, 2023)
Malaysia’s 15th General Election (GE15) was held on 19 Sept 2022, and the results showed that no political party gained the simple majority to form a government. DAP veteran Lim Kit Siang suggested a coalition government of PH (82), PN (74), and the Borneo bloc (35) under Anwar Ibrahim as the Prime Minister to form a coalition with a specific programmed to reverse Malaysia’s decline, and to make Malaysia a great world-class nation, and to fight corruption. Unfortunately, PN coalition partner, Parti Islam Se-Malaysia (PAS) disagreed to cooperate with PH due to the slogans “no Anwar” and “no DAP”. PAS seriously refused to establish a political cooperation with PH even though they realized that their refusal would result in a hung parliament. As a reality, GE15 was different from the previous GE because only the parliament was dissolved while not all states dissolved their state assemblies. By sweeping clean all the parliamentary seats in Kelantan and Terengganu, PAS really intended to be the ruling government. However, Hadi made a big mistake when he stuck to the stance that his party is more than willing to become as part of the opposition instead of forming a coalition government with PH. Therefore, this research found that PAS has achieved a great performance in GE15, but they failed to become a part of the coalition government and now being an opposition leader due to the mistakes made by the PAS president.